Relationship of Root Mean Square Value of Electromyography and Isometric Torque of Quadriceps in Normal Subjects - Qiurong XIE; Zheng JIANG; Qinglu LUO (康复学报)
Objective:To investigate the relationship between electromyography (EMG) signal of the rectus femoris muscle and the muscle strength of the quadriceps at different torque levels of maximal isometric voluntary contraction (100%, 75%, 50%, 25%MVC) in normal young subjects.Methods:Five normal healthy young subjects were recruited in this study. The extension torque and surface electromyography (sEMG) of the right quadriceps muscles were measured during the four torque levels of isometric contraction, at 100%, 75%, 50%, 25%MVC.Results:There was a significant correlation between RMS values and the contraction force of quadriceps muscles (P<0.01). There was a strong correlation between the extension torque (MVC) and RMS voltages (EMG) (γ=0.874).Conclusion:A linear relationship between contraction force and the RMS value of the EMG signal of the quadriceps muscles is observed in normal subjects with the required torque of 100%, 75%, 50%, 25%MVC.